Pengaruh Promo Diskon dan Gratis Ongkos Kirim di E-Commerce Shopee Terhadap Minat Beli Masyarakat di Kecamatan Beji Kota Depok - Armelia Putri; Desy Suryani (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
Shopee is one of the e-commerce companies that continues to increase in Indonesia. Shopee focuses more on the mobile platform so that people find it easier to search, shop and sell directly on their mobile phones. This study aims to analyze the "Effect of Promo Discounts and Free Shipping on E-commerce Shopee on Buying Interests of the People in Beji District, Depok City."This study used a survey method, using a questionnaire as an instrument for collecting data. In determining the sample using purposive sampling method. As for the respondents, there were 60 people from the Beji sub-district community, Depok City, for data management using the SPSS version 25 for windows program.The result is that H1 is accepted because t count is 2.606> 2.002 t table, which means that discounts affect purchase intention, H2 is accepted because the t count is 3.862 > t table 2.002 which means free shipping has an effect on buying interest, H3 is accepted because the t count value 3.694 <t table 2.002 and H4 is accepted because the calculated F value is 19.363> 3.16.